DIGITALISATION OF HUMAN RESOURCE MANAGEMENT AS A FACTOR OF ENHANCING THE ECONOMIC RESILIENCE OF ENTERPRISES UNDER WARTIME CONDITIONS: ADAPTATION OF EUROPEAN PRACTICES - Anastasiia Zerkal; Mariia Pavlenko (Three Seas Economic Journal)
The purpose of the paper is to explore the transformation of human resource management (HRM) practices in the context of digitalisation, with a specific focus on European enterprises and the potential adaptation of these practices in Ukraine under wartime conditions. The study examines how digital tools, ranging from AI-powered recruitment platforms to integrated HR systems, have changed the operational landscape of HR departments and contributed to organizational resilience. Methodology. The research is based on a comparative analysis of secondary data, case studies, and recent literature on digital HRM tools implemented across European countries. A structured evaluation of selected platforms (e.g., SAP SuccessFactors, LinkedIn Talent Solutions, Oracle HCM) was conducted, focusing on their advantages, limitations, and applicability in crisis settings. The results highlight the strategic shift toward employee-centered digitalisation and reveal how large European enterprises have successfully leveraged digital HR tools to ensure continuity, engagement, and performance. These practices, however, face limitations in wartime Ukraine due to infrastructural constraints, workforce displacement, and legal misalignment. The paper identifies hybrid solutions combining global platforms with localized modules as the most promising approach for Ukrainian companies. Practical implications. The findings offer evidence-based recommendations for enterprises operating in volatile environments, particularly those in Ukraine, suggesting gradual digital adoption, integration with national systems, and employee-centered implementation strategies. Emphasis is placed on balancing technological innovation with psychological safety and adaptability of human capital. Value / originality. The paper contributes to the understanding of how digital HRM can be implemented in complex environments shaped by both digital transition and geopolitical disruption, offering original insight into adapting European practices to the Ukrainian context under martial law.